ANALYZING THE INTEGRITY OF PUBLIC ACCOUNTANT AT “CEMERLANG” PUBLIC ACCOUNTANT FIRM IN SURABAYA (PHENOMENOLOGY STUDY) - Aripratiwi, Ratna Anggraini (Journal of Innovation in Business and Economics, 2017)
This study aims to explore the deep meaning of the integrity attitudes that is experienced, felt, and performed by a public accountant in one of the famous KAP in Surabaya, KAP "Cemerlang". Revealing the attitude of the integrity of public accountant is important since there are large number of public accountants who are still dragged into fraud and violations, resulting in unethical decisions. Every public accountant has a different perspective in determining and practicing an attitude of integrity, whether to defend or even release it for a particular purpose that ultimately raises a variety of meanings of pure integrity and pragmatic integrity.